The Effect of Ultraviolet Light Exposure on the Titanium Screw Implants Osseointegration in Different Time Intervals - M Shakir Mahmood; Y Mohammed Haider; HK Alalwan; A Fatalla; N Mokhtar (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: The effect of ultraviolet light on the osseointegration of titanium screw implants is scarcely discussed in literature. The present research was performed to study the effect of Ultraviolet (UV) light exposure on the osseointegration of titanium dental implants in different time intervals. Methods: In this in vivo experimental-qualitative study including UV exposure and mechanical and histological tests, 48 implant screws were implanted in the tibia of 48 rabbits for histological and torque removal tests. The rabbits were divided into two groups (mechanical n=36 and histological n=12). A bone-cutting process was performed 5 mm from an implant screw. Block was preserved in 10% formalin, decalcified in 8% formic acid, and the screw was carefully removed. Bone dehydration was performed using alcohol, heated for 30 minutes, and infiltrated with xylene and paraffin wax before embedding. Each of the mechanical and histological tests contained three groups (Control, UV 30, and UV 60) for each healing period, 2 and 6 weeks. Findings: The mean value for torque removal test for screws in the UV60 group in 2 weeks significantly increased compared to the control group (7.48±1.64 vs. 2.41±0.70). The mean value of new bone formation percentage (NBFP) for the UV60 implanted rabbits was 5.76%, compared to the control group 3.65% in the second time interval (6 weeks after implantation). Histological examination showed that bone formation, mineralization, and maturation have been increased with the rabbits exposed to UV light for 30 (4.71± 0.85) and 60 minutes (5.76±0.85) compared with the control group (3.65±0.55). Conclusion: The results of this study showed that UV light exposure can effectively reduce the period of rabbit implants osseointegration.